Bubble detection in housing prices: Evidence for OECD countries between 1970 and 2015 - Quintana Caris, Mario (Estudios de Administración, 2017)
Using a structural-break econometric methodology, proposed by Homm and Breitung (2012), in nominal house price series since 1970 through the second quarter of 2015 we find price bubbles in 14 out of the 18 advanced economies under study. This result is consistent with the one obtained by Engsted et al. (2015), who uses a cointegration between price and rent that allows the presence of an explosive component that they identify as a price bubble. We conclude that our results are important because they put the nominal price analysis as an early indicator of the presence of house price bubbles.